Britain's Mammals : A Field Guide to the Mammals of Britain and Ireland - Couzens, Dominic (Book collections on Project MUSE., 2017)
This book is a photographic field guide to all the mammals recorded in the wild in Britain and Ireland in recent times--including marine mammals, bats and introduced species that have bred. It includes status, population, distribution and conservation designations for each species, and features hundreds of photographs and incorporates invaluable tips and suggestions to help you track down and identify even the most difficult species.